EFFECT OF RETURN ON ASSET, OPERATING CASH FLOWS AND EARNING ON RETURN OF SHARES WITH LEVERAGE AS MODERATING VARIABLES IN MINING COMPANIES - Sitanggang Desmayanti; Irawati Irawati; Layla Hafni; Helly Aroza Siregar; Febdwi Suryani (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to analyze Return On Asset (ROA), Operating Cash Flow and Earning Per Share (EPS) on stock returns with Leverage (DAR) as a moderating variable in mining companies listed on the Indonesia Stock Exchange (BEI). The population used is 49 mining companies on the IDX for the 2017-2019 period. Sampling in this study used a purposive sampling method with the criteria for mining companies listed on the Indonesia Stock Exchange for the 2017-2019 period and companies that were delisted during the 2017-2019 period and the availability of required Annual Financial Report data for the 2017-2019 period. Based on these criteria, the number of samples in this study was determined by 41 companies. The analysis technique used in this research is moderating variable regression analysis with interaction tests with the help of SmartPLS software. The results showed that analyzing Return On Asset (ROA) and Operating Cash Flow had a positive and insignificant effect on stock returns, while the EPS variable had a negative and insignificant effect on stock returns, and leverage as a moderating variable had a positive and insignificant effect on the relationship Return On Asset (ROA), Operating Cash Flow and Earning Per Share (EPS) on the return of mining companies on the Indonesia Stock Exchange for the 2017-2019 period. Penelitian ini bertujuan untuk menganalisis Return On Asset (ROA), Operating Cash Flow, dan Earning Per Share (EPS) terhadap return saham dengan Leverage (DAR) sebagai variabel moderasi pada perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia (BEI). Populasi yang digunakan adalah 49 perusahaan pertambangan di IDX untuk periode 2017-2019. Pengambilan sampel dalam penelitian ini menggunakan metode purposive sampling dengan kriteria perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia untuk periode 2017-2019 dan perusahaan yang telah dihapus dari daftar (delisted) selama periode 2017-2019 serta ketersediaan data Laporan Keuangan Tahunan (APBN) yang dibutuhkan untuk periode 2017-2019. Berdasarkan kriteria tersebut, jumlah sampel dalam penelitian ini ditentukan sebanyak 41 perusahaan. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi variabel moderasi dengan uji interaksi dengan bantuan perangkat lunak SmartPLS. Hasil penelitian menunjukkan bahwa analisis Return On Asset (ROA) dan Operating Cash Flow memiliki pengaruh positif dan tidak signifikan terhadap return saham, sedangkan variabel EPS memiliki pengaruh negatif dan tidak signifikan terhadap return saham, dan leverage sebagai variabel moderasi memiliki pengaruh positif dan tidak signifikan terhadap hubungan Return On Asset (ROA), Operating Cash Flow dan Earning Per Share (EPS) pada return perusahaan pertambangan di Bursa Efek Indonesia untuk periode 2017-2019.